Web-based decision support system tools: The Soil and Water Assessment Tool Online visualization and analyses (SWATOnline) and NASA earth observation data downloading and reformatting tool (NASAaccess). (October 2019) - McDonald, Spencer; Mohammed, Ibrahim Nourein; Bolten, John D.; Pulla, Sarva; Meechaiya, Chinaporn; Markert, Amanda; Nelson, E. James; Srinivasan, Raghavan; Lakshmi, Venkat
Abstract: The current influx of climate related information required scientists to communicate their findings to decision makers in governments, disaster preparedness organizations, and the general public. The Soil and Water Assessment Tool (SWAT) is a powerful modelling tool that allows scientists to simulate many of the physical processes involved in the water cycle. This article presents the design, methods and development efforts to overcome some of the limitations of the previously developed SWAT visualization software programs by creating a set of modular web applications that can be duplicated, customized, and run. Moreover, this article features a web application development tool for climate data retrieval. The NASAaccess fetches, extracts and reformats climate data from the National Aeronautics and Space Administration servers and outputs data compatible with hydrological models. This work has the potential to increase the SWAT's model impact on non-technically trained stakeholders and decision makers charged with water and climate management. Highlights: SWATonline & NASAaccess Tethys web apps developed for hydroclimatic applications. The web apps are modular and can be hosted anywhere (public or private servers). Web apps provide easy access and retrieval capabilities to climate data. Web apps address needs for SWAT easy access and visualization functionalities.